2022
DOI: 10.1039/d2ra05037d
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescent aptasensor based on gold nanoparticles quenching the fluorescence of rhodamine B to detect acetamiprid

Abstract: In this paper, we present a turn-on fluorescent approach to detect acetamiprid in traditional Chinese medicine, with a high sensitivity and low detection limit. It provides more application possibilities for fluorescence-aptamer biosensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It has been found that Rhodamine B could be adsorbed on the AuNP surface by electrostatic interaction. 44 The maximum emission wavelength was monitored at 578 nm using a fluorescence spectrophotometer when excited at 510 nm. The results and proposed mechanism for fluorescence detection are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that Rhodamine B could be adsorbed on the AuNP surface by electrostatic interaction. 44 The maximum emission wavelength was monitored at 578 nm using a fluorescence spectrophotometer when excited at 510 nm. The results and proposed mechanism for fluorescence detection are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The uorescence of rhodamine B is quenched by gold nanoparticles because of the resonance energy transfer between them. 44 Thus, AuNPs have the unique property of an extremely high extinction coefficient, leading to the quenching of uorescent species at different emission wavelengths from the visible range to the near infrared. 45,47 The extremely high extinction coefficient and broad absorption spectrum overlap well with the emission of the usual uorophore, resulting in excellent uorescence quenching ability.…”
Section: Mechanism For the Uorescence Detection Of Aunps And Three T...mentioning
confidence: 99%